Fetal Bovine Serum Meningkatkan Maturasi Inti Oosit Kelinci Setelah Dimaturasi Secara In Vitro - Kurniani Karja, Ni Wayan; Plumeria Aqshani, Winny; Pratiwi Kusumawati, Yesi; Gilang Pravitasari, Veronika; Gustari, Sri (Jurnal Veteriner, 2010)
This study was conducted to examine the meiotic competence or nuclear maturation of rabbit oocytesmatured in vitro. Oocytes were recovered by mincing the ovaries in modified phosphate buffer saline (m-PBS). Selected cumulus-oocyte complexes (COCs) with compact cumulus cell mass and a dark, homogenousooplasm were cultured in maturation medium at 38°C in a humidified atmosphere of 5% CO2 in air, andthen stained for nuclear maturation. Three experiments were carried out. In Experiment 1, COCs werecultured in maturation medium for 18-20, 22-24, and 28-30 h. The proportion of oocytes at metaphase II(MII) was similar (P>0.05) at 18-20 (69.2%), 22-24 (66.4%), and 28-30 (71.1) h of culture. In Experiment 2,COCs were cultured in either maturation medium containing 0.04% bovine serum albumine (BSA) or 5%fetal bovine serum (FBS) for 24 h. The proprotion of oocytes that reached MII were higher (P<0.05) in FBSgroup (79.2%) than those of oocytes in BSA group (64%). In Experiment 3, based on the presence or absenceof follicles and corpora lutea, the ovarian pairs were classified into follicular or luteal stages. There was nodifference (P>0.05) among oocytes collected from ovaries in follicular (79.7%) and luteal stages (78.7%) inthe ability to achieve nuclear maturation. These results indicated that nuclear maturation of rabbitoocytes in vitro was completed at 18-20 h of maturation culture and was not affected by ovary’s reproductivestage. The presence of FBS in the maturation medium enhanced the ability of rabbit oocytes to achievenuclear maturation.
Keywords: in vitro maturation, rabbit oocytes, bovine serum albumin, fetal bovine serum.